2021
DOI: 10.1002/cnr2.1388
|View full text |Cite
|
Sign up to set email alerts
|

Rapid real‐world data analysis of patients with cancer, with and without COVID‐19, across distinct health systems

Abstract: Background The understanding of the impact of COVID‐19 in patients with cancer is evolving, with need for rapid analysis. Aims This study aims to compare the clinical and demographic characteristics of patients with cancer (with and without COVID‐19) and characterize the clinical outcomes of patients with COVID‐19 and cancer. Methods and Results Real‐world data (RWD) from two health systems were used to identify 146 702 adults diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…This single arm, retrospective study used the US Syapse Learning Health Network (LHN) to evaluate patient characteristics, treatment patterns, and clinical outcomes among patients receiving first-line therapy with palbociclib plus an aromatase inhibitor for A/MBC. The Syapse LHN is a longitudinal database capturing cancer care and noncancer care data and has previously been used by the US Food and Drug Administration [ 21 , 22 , 23 ]. It includes patients from large community health systems based in the United States that include managed care delivery networks across 25 states, 457 hospitals, and more than 1300 oncologists.…”
Section: Methodsmentioning
confidence: 99%
“…This single arm, retrospective study used the US Syapse Learning Health Network (LHN) to evaluate patient characteristics, treatment patterns, and clinical outcomes among patients receiving first-line therapy with palbociclib plus an aromatase inhibitor for A/MBC. The Syapse LHN is a longitudinal database capturing cancer care and noncancer care data and has previously been used by the US Food and Drug Administration [ 21 , 22 , 23 ]. It includes patients from large community health systems based in the United States that include managed care delivery networks across 25 states, 457 hospitals, and more than 1300 oncologists.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, patients with cancer during the pandemic experienced more problems with access to care due to a variety of reasons, such as difficulty in obtaining timely appointments due to the healthcare shifts in focusing on COVID‐19 specific care, leading to potential delayed diagnosis and treatments 4 . Sociodemographic factors such as zip code of residency, non‐Hispanic (NH) Black race/ethnicity, and male sex have also been associated with hospitalization and mortality, however, their study has been limited in the pandemic 5 . Han et al quantified deaths due to COVID‐19 and cancer using data from 2020, prior to the widespread availability of vaccination, and found that factors such as American Indian or Alaskan Native, Black, and Hispanic race/ethnicity, age greater than or equal to 85, and residence in a large central metropolitan area were significant risk factors for mortality in patients with cancer and COVID‐19 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality was reported in nine studies including 393 patients on ICIs and 1025 controls. [10,11,[13][14][15]17,22,23,26] Retrospective cohorts Albiges 2020 [10] 178 19 (10.7) Chemotherapy, targeted therapy, hormone therapy Hospital admission, clinical worsening, ICU admission Assaad 2020 [11] 55 3 (5.5) Chemotherapy, no treatment Mortality Dai 2020 [13] 105 6 (5.7) Chemotherapy, targeted therapy, chemotherapy þ immunotherapy, healthy controls…”
Section: Ici Therapy Versus Chemotherapymentioning
confidence: 99%
“…Gonzalez-Cao 2020 [24] 50 22 (44) Targeted therapy, no treatment Mortality Grivas 2021 [15]a 4966 238 (4.8) Chemotherapy, targeted therapy, no treatment, hormone therapy Mortality, ICU admission, hospital admission, mechanical ventilation Gulati 2021 [16] 4217 199 (4.7) Targeted therapy, hormone therapy Thrombotic complications, ICU admission, mortality Hwang 2021 [17]b 1267 12 (1) Chemotherapy, targeted therapy, no treatment…”
Section: Hospital Admissionmentioning
confidence: 99%
See 1 more Smart Citation